Karakteristik dan Budaya Keselamatan Pasien terhadap Insiden Keselamatan Pasien - Arni Wianti; Asep Setiawan; Murtiningsih Murtiningsih; Budiman Budiman; Lilis Rohayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the factors that influence patient safety culture on patient safety incidents in Cirebon City and Regency public hospitals which are seen from the characteristics of nurses and patient safety culture. The type of research used is non-experimental quantitative using a cross-sectional research design. The results showed that the characteristics of nurses that influenced patient safety incidents were education with an OR of 5,613 and gender with an OR of 4,478. In conclusion, education, gender, management support, cooperation between units as well as handsoff and transition are factors that influence patient safety incidents. Keywords: Patient Safety Culture, Patient Safety Incident, Nurse Characteristics